1997
DOI: 10.1172/jci119594
|View full text |Cite
|
Sign up to set email alerts
|

Somatic deletion of the imprinted 11p15 region in sporadic persistent hyperinsulinemic hypoglycemia of infancy is specific of focal adenomatous hyperplasia and endorses partial pancreatectomy.

Abstract: Sporadic persistent hyperinsulinemic hypoglycemia of infancy (PHHI) or nesidioblastosis is a heterogeneous disorder characterized by profound hypoglycemia due to inappropriate hypersecretion of insulin. An important diagnostic goal is to distinguish patients with a focal hyperplasia of islet cells of the pancreas (FoPHHI) from those with a diffuse abnormality of islets (DiPHHI) because management strategies differ significantly. 16 infants with sporadic PHHI resistant to diazoxide and who underwent pancreatect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
173
1
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 281 publications
(188 citation statements)
references
References 56 publications
(65 reference statements)
10
173
1
4
Order By: Relevance
“…IGF2 has also been reported with human overgrowth syndromes including Beckwith-Wiedeman syndrome, which has also been associated with nesidioblastosis. 13,[28][29][30] Studies in mice and transgenic mouse models has shown that the family of IGFs and IGF-binding proteins are involved in cellular functions including insulin and glucose regulation. 31 Direct evidence of the role of IGF2 and IGF-binding proteins on proliferation of insulinproducing cells has been reported in mice with disruption of the MEN1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…IGF2 has also been reported with human overgrowth syndromes including Beckwith-Wiedeman syndrome, which has also been associated with nesidioblastosis. 13,[28][29][30] Studies in mice and transgenic mouse models has shown that the family of IGFs and IGF-binding proteins are involved in cellular functions including insulin and glucose regulation. 31 Direct evidence of the role of IGF2 and IGF-binding proteins on proliferation of insulinproducing cells has been reported in mice with disruption of the MEN1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason it was surprising to find that patients with PHHI due to adenoma (usually sporadic) are heterozygous for a point mutation in SUR, which is always on the paternal chromosome (36). The maternal allele is normal in these patients' germline, but clonally lost in the adenoma cell lineage, through a large deletion that involves the nearby imprinted cluster on 11p15.5 (37). Taken together these observations invite us to propose that the generation of the adenoma requires two molecular events.…”
Section: The Focal Form Of Persistent Hyperinsulinemic Hypoglycemia Omentioning
confidence: 99%
“…The resulting loss of heterozygosity (LOH) renders the b-cells biallelic for the abnormal foci, altering the K ATP channel and resulting in dysregulated insulin secretion within the focal lesion (16,17,18). The consequent imbalance in the expression of adjacent imprinted genes implicated in cell proliferation (such as CDKN1C and H19 normally expressed from the maternal allele and IGF2 paternally expressed) within the 11p15.5 region leads to focal islet cell adenomatous hyperplasia (19,20,21,22). Focal CHI is usually medically unresponsive, although diazoxide-responsive focal CHI has been recently described (23).…”
Section: Introductionmentioning
confidence: 99%